Effect of ethylmethylhydroxypyridine succinate on the functional activity of the transporter P-glycoprotein in the blood-brain barrier of rats under normal conditions and under hypoxic hypoxia - P. Yu. Mylnikov; A. V. Shchulkin; I. V. Chernykh; E. N. Yakusheva (Фармакокинетика и Фармакодинамика)
Relevance. Ethylmethylhydroxypyridine succinate (EMHPS) is a reference domestic drug with pronounced antioxidant and antihypoxic activity. P-Glycoprotein (Pgp) is an ATP-dependent transport protein localized in tissue barriers and protecting cells and organs from the effects of xenobiotics. Being expressed in the blood-brain barrier (BBB), Pgp limits the penetration of drugs and toxic substances into the brain tissue. Aim – to evaluate the effect of EMHPS on the functional activity of Pgp in the BBB of rats in normal conditions and in acute hypoxic hypobaric hypoxia in the experiment. Methods. The studies were carried out on male Wistar rats weighing 200–250 g, which were divided into 4 groups: group 1 (control, n = 30) – intact rats; Group 2 (control of hypoxia, n = 30) – rats, which were simulated hypoxia and before that they were once injected with water for injection; Group 3 (n = 30) – intact animals, which were injected intravenously with EMHPS at a dose of 50 mg / kg body weight; Group 4 (n = 30) – rats, which were injected intravenously with EMHPS at a dose of 50 mg/kg body weight before modeling hypoxia. 30 minutes after injection, animals of groups 2 and 4 were simulated acute hypoxic hypoxia for 30 minutes by ascending to an altitude of 8000 m with an ascent and descent speed of 50 m/s. 3 h after descent animals of groups 2 and 4 and 30 min after intravenous injection in animals of groups 1 and 3, the functional activity of Pgp in the BBB was assessed by the penetration of fexofenadine, a marker substrate of Pgp, into the brain tissue. For this, fexofenadine was injected into the tail vein of rats at a dose of 10 mg/kg of body weight. After 5, 10, 15, 30, 45, 60 minutes after administration, they were euthanized, at least 4 ml of blood was taken from the abdominal aorta into heparinized tubes and the cortex of the frontal lobes of the brain. The concentration of fexofenadine in biosamples was analyzed by HPLC-UV according to original methods. Results. In the course of the study, it was shown that a single intravenous injection of EMHPS at a dose of 50 mg/kg of body weight causes an increase in the content of fexofenadine in the cerebral cortex of rats, which indicates a decrease in the activity of the Pgp transporter protein. Simulation of acute hypoxic hypoxia was also accompanied by an increase in the permeability of the transport protein substrate into the brain tissue. At the same time, the prophylactic administration of EMHPS before hypoxic exposure did not significantly affect the BBB permeability, which remained significantly higher than the control and did not differ from the permeability during isolated hypoxic exposure. Conclusions: EMHPS with a single intravenous injection at a dose of 50 mg/kg body weight reduces the activity of Pgp in the BBB in normal conditions and does not significantly affect the penetration of the transporter substrate – fexofenadine into the brain tissue in acute hypoxic hypoxia